The roman theatre of Bracara Augusta - Martins, Manuela (2014)
This paper aims to present the main features of the roman theatre of Bracara Augusta identified in 1999. Although it is still under study, a significant set of evidence made it possible to present its characteristics, to value the socioeconomic issues related with its construction and to discuss the aspects related to the development of the NW Iberian Peninsula cities, where traditionally this type of equipment was believed to be absent, and to understand the diffusion of roman public architecture models in peripheral regions within the Western Empire.